Metal Organic Framework Derivative Improving Lithium Metal Anode Cycling. (23rd January 2020) - Zhong, Yiren; Lin, Fang; Wang, Maoyu; Zhang, Yifang; Ma, Qing; Lin, Julia; Feng, Zhenxing; Wang, Hailiang
Abstract: This work demonstrates a new approach in using metal organic framework (MOF) materials to improve Li metal batteries, a burgeoning rechargeable battery technology. Instead of using the MIL‐125‐Ti MOF structure directly, the material is decomposed into intimately‐mixed amorphous titanium dioxide and crystalline terephthalic acid. The resulting composite material outperforms the oxide alone, the organic component alone, and the parent MOF in suppressing Li dendrite growth and extending cycle life of Li metal electrodes. Coated on a commercial polypropylene separator, this material induces the formation of a desirable solid electrolyte interphase layer comprising mechanically flexible organic species and ionically conductive lithium nitride species, which in turn leads to Li||Cu and Li||Li cells that can stably operate for hundreds of charging–discharging cycles. In addition, this material strongly adsorbs lithium polysulfides and can also benefit the cathode of lithium–sulfur batteries. Abstract : A new composite material consisting of intimately mixed amorphous titanium dioxide and crystalline terephthalic acid, derived from a metal organic framework structure, is demonstrated to be useful in extending the cycle life of both lithium metal electrodes and lithium–sulfur batteries.